STUDYING OF THE THREE-DIMENSIONAL ORGANISATION OF PARENCHYMATOUS AND HOLLOW ORGANS OF THE PERSON BY MEANS OF AN INJECTION-CORROSION METHOD - Sherstjuk, O.O.; Tarasenko, Yа.A.; Dejnega, T.F.; Svintsitskаyа, N.L.; Тихонова, О.О.; Рогуля, В.О. (World of Medicine and Biology, 2012)
To the basic methods of research in stereomorphology carry an injection-corrosion method which allows to receive three-dimensional representation about micro- and macroanatomic structures. Despite difficulties of methodological character, it is possible to receive injection-corrosion preparations of almost all organs of the human that is of great importance in experimental and clinical medicine.
Keywords: three-dimensional organisation; organs of the human; corrosion method